To find the solution set where \( f(x) = g(x) \), we need to compare the values of \( f(x) \) and \( g(x) \) for the given \( x \) values in both tables.
From the first table for \( f(x) \):
- \( f(-1) = -12 \)
- \( f(1) = -2 \)
- \( f(3) = 4 \)
- \( f(5) = -2 \)
- \( f(6) = -12 \)
From the second table for \( g(x) \):
- \( g(-1) = -8 \)
- \( g(0) = -5 \)
- \( g(1) = -2 \)
- \( g(2) = 1 \)
- \( g(3) = 4 \)
Now we will look for \( x \) values such that \( f(x) = g(x) \).
-
For \( x = -1 \):
- \( f(-1) = -12 \)
- \( g(-1) = -8 \)
- Not equal.
-
For \( x = 1 \):
- \( f(1) = -2 \)
- \( g(1) = -2 \)
- Equal, so \( x = 1 \) is a solution.
-
For \( x = 3 \):
- \( f(3) = 4 \)
- \( g(3) = 4 \)
- Equal, so \( x = 3 \) is a solution.
-
For \( x = 5 \):
- \( f(5) = -2 \)
- Not in \( g(x) \).
-
For \( x = 6 \):
- Not in \( g(x) \).
The only values of \( x \) where \( f(x) = g(x) \) are 1 and 3.
Thus, the solution set is: \[ { 1, 3 } \]